2005
DOI: 10.1086/429324
|View full text |Cite
|
Sign up to set email alerts
|

Gastroenteritis Due to Listeria monocytogenes

Abstract: It has been known for a long time that many patients experience diarrhea antecedent to the development of bacteremia or meningoencephalitis due to Listeria monocytogenes, but it was only recently that convincing evidence was obtained that this organism can cause acute, self-limited, febrile gastroenteritis in healthy persons. At least 7 outbreaks of foodborne gastroenteritis due to L. monocytogenes have been reported. Illness typically occurs 24 h after ingestion of a large inoculum of bacteria and usually las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
126
0
13

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(142 citation statements)
references
References 28 publications
0
126
0
13
Order By: Relevance
“…(1995) showed that 97% of resistant starch assayed in foods was recovered in ileal fluids. (Miliotis and Bier, 2003) (d) Typically 1-2 days or may be prolonged (FDA, 2002) (e) 3-6 days (WHO, 2008); 2-6 days (Miliotis and Bier, 2003) (f) Typically 1-3 days, up to 1 week (Ooi and Lorber, 2005) …”
Section: Resultsmentioning
confidence: 99%
“…(1995) showed that 97% of resistant starch assayed in foods was recovered in ileal fluids. (Miliotis and Bier, 2003) (d) Typically 1-2 days or may be prolonged (FDA, 2002) (e) 3-6 days (WHO, 2008); 2-6 days (Miliotis and Bier, 2003) (f) Typically 1-3 days, up to 1 week (Ooi and Lorber, 2005) …”
Section: Resultsmentioning
confidence: 99%
“…Although, antecedent diarrhoea has been reported in invasive form of listeriosis (Schwartz et al, 1989), however in recent past it has been convincingly proven that L. monocytogenes can cause a non-invasive acute, self-limiting, febrile gastroenteritis in healthy individuals including immunocompromised hosts (Ooi and Lorber, 2005). After ingestion of L. monocytogenes through contaminated food, the intestinal tract serve as a major portal of entry, wherein L. monocytogenes penetrate the mucosal tissue either directly, via invasion of enterocytes, or indirectly, via active penetration of the Peyer's patches.…”
Section: Introductionmentioning
confidence: 99%
“…Salmonella and Shigella species, Escherichia coli (Pickering, 2004), Listeria monocytoglues (Ooi & Lorber, 2005), Yersinia enterocolytica (Abel-Haq et al, 2000) are the pathogens involved with this disease. The use of antimicrobial agents for treatment of the diarrhea is limited because of the resistance among enteric pathogens.…”
Section: Resultsmentioning
confidence: 99%